Middle Atmosphere Focus workshop: stretching the scientific capabilities of a middle atmosphere resolving General Circulation Model. (28th January 2013) - Bushell, A. C.; Hardiman, S. C.
Abstract The 2011 Royal Meteorological Society conference Middle Atmosphere Focus workshop reviewed progress over the six years since Exeter last hosted the conference and addressed prospects for the next six years with an invitation for interactive discussion on areas that offer promise for expanding the scientific capabilities of middle atmosphere configurations in general circulation models or which might imply new scientific challenges for the decade. In order to initiate discussion, invited speakers gave presentations that offered a flavour of developing areas, covering middle atmosphere interactions with extended-range forecast prediction, tracer advection, impact of solar variability and geoengineering insights from volcanic eruptions.Copyright © 2012 Royal Meteorological Society